Analysis of family law related to divorce due to parental interference - Rina Septiani; Fira Mubayyinah (Institute Of computer Science (IOCS), 2024)
This research aims to describe the form parental intervention in the child's household cause divorce and analysis of Islamic family law regarding parental intervention in household of children which causes divorce. This research is a normative-empirical type of research. This research describes and describes how parents intervene in the household children who cause divorce. This research describes and describes how parents intervene in the household children who cause divorce are then analyzed through family law This research produced two findings. First, Parental intervention in a child's household can lead to divorce. This is based on the child's mindset who still depend on parents and children who still live with other people. secondly based on family law analysis parental intervention in their child's household is not could be a reason for divorce, but this conflict triggers the birth of reasons be grounds for divorce. actually parental intervention in their child's household is permitted but first we will see how far the intervention has gone. Divorce due to parental intervention is not included in the classification of reasons for divorce, However, this problem will fall under Article 116 KHI letter (f), namely constant quarrels and no hope of getting along again.